SISTEM INFORMASI MONITORING DAN LAPORAN PROYEK FIBERISASI DI PT. EKSPANINDO PRIMA MULTIMEDIA - Perdana Bagja Kusumah; Puspa Eosina; Jejen Jaenudin (Universitas Widyatama, 2020)
PT.Ekspanindo Prima Multimedia is a company engaged in the telecommunications sector which provides integrated services in fiber optic network development projects in several cities in Indonesia. To control the fiberization project that is carried out requires a volume of project work data, starting from planning, implementation, and the end of the project. In a three-stage process, job data can be applied to the system using the sequential systems model development method consisting of analysis, design, implementation, and testing. The application of information systems science in the data processing of this fiberization project is (1) analyzing and designing an information system with a linear sequential method which results in functional requirements analysis, user analysis, and system design using UML diagrams, and implemented using computer language. (2) the system that is built displays information in the form of a list of the volume of planning data, implementation, end of the project, and the difference data to be able to monitor the work of fiberization projects needed by PT. Ekpanindo Prima Multimedia.